2023
DOI: 10.1038/s41598-023-30404-6
|View full text |Cite
|
Sign up to set email alerts
|

Magnetic solid phase extraction of Sunitinib malate in urine samples assisted with mixed hemimicelle and spectrophotometric detection

Abstract: The mixed hemimicelle-based solid phase extraction method using the coated sodium dodecyl sulfate by magnetic iron oxide nanoparticles as adsorbent was developed for extraction and determination of Sunitinib malate in real samples prior to determination by UV–Visible spectrophotometry. For the characterization of synthesized nanoparticles, Fourier transform infrared spectroscopy, and scanning electron microscopy was used. The influences of different factors affecting the extraction efficiency of Sunitinib mala… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 47 publications
0
3
0
Order By: Relevance
“…From the UV−vis spectrum, a distinct absorption peak of sunitinib was detected at approximately 421 nm (Figure S1), which is in agreement with previously described. 28 As in previous studies, 29,30 the peak absorption of sunitinib at 421 nm was used to quantify the sunitinib content to estimate the encapsulation efficacy of liposomes. The results showed that the encapsulation efficacy of liposomes gradually increased with the increasing amount of lipids, and the efficacy seemed to level off when the mass ratio of sunitinib to lipids reached 1:10 (Figure 1g).…”
Section: Resultsmentioning
confidence: 99%
“…From the UV−vis spectrum, a distinct absorption peak of sunitinib was detected at approximately 421 nm (Figure S1), which is in agreement with previously described. 28 As in previous studies, 29,30 the peak absorption of sunitinib at 421 nm was used to quantify the sunitinib content to estimate the encapsulation efficacy of liposomes. The results showed that the encapsulation efficacy of liposomes gradually increased with the increasing amount of lipids, and the efficacy seemed to level off when the mass ratio of sunitinib to lipids reached 1:10 (Figure 1g).…”
Section: Resultsmentioning
confidence: 99%
“…[25][26][27] Many sample preparation methods such as solid phase extraction (SPE), liquid-liquid extraction (LLE), and cloud point extraction (CPE) have been developed for separation and enrichment of copper from complex matrix media. [28][29][30][31] However, all these classical methods have initiated to leave their position to microextraction methods because of the disadvantages such as time consuming, laborious, expensive, toxic, insufficient preconcentration factor, high organic solvent volume and secondary waste. [32][33] For these disadvantages to eliminate, microextraction techniques developed such as liquid phase micro extraction (LPME) and magnetic dispersive micro solid-phase extraction (M-D-μSPE), which offer the advantages of environmentally friendly, simple, fast, cheap, high preconcentration factor, high analyte recovery, minimal analyte loss and low volume toxic solvent use.…”
Section: Many Analytical Techniques Such As Faas Gf-aas Icp-oes Icp-msmentioning
confidence: 99%
“…Magnetic solid phase extraction enables the removal of adsorbents from the solution by means of magnetic nanoparticles, without the need for centrifugation or any filtering process, only with the application of an external magnetic field. [29][30][31] This technique provides adsorption process with high removal efficiency, easy separation, higher surface area with magnetic nanoparticles for higher adsorption capacity, and suitability for different surface modification. [29,32] In literature, only few adsorptive removal studies have been shown recently for fipronil from aqueous solution in which modified zeolites were used as adsorbents mostly.…”
Section: Introductionmentioning
confidence: 99%
“…In adsorption based separation processes, different types of adsorbents are used and the selection of the adsorbent depends on the porosity, pore structure, nature of its adsorbing surfaces, surface functional groups and most importantly applications. Magnetic solid phase extraction enables the removal of adsorbents from the solution by means of magnetic nanoparticles, without the need for centrifugation or any filtering process, only with the application of an external magnetic field [29–31] . This technique provides adsorption process with high removal efficiency, easy separation, higher surface area with magnetic nanoparticles for higher adsorption capacity, and suitability for different surface modification [29,32] …”
Section: Introductionmentioning
confidence: 99%